Rendimiento de tres ecotipos de maíz forrajero (Zea mays L.) en tres localidades del cantón Loja. - Peña González, Richard Fabricio (2020)
Livestock productions is one of the main economic activities in several areas of Loja canton, however, at certain times there is a shortage of cattle feed, so the production of maize (Zea mays L.) can be an alternative to improve the fodder supply. The environment can modify the phenotypic characteristics of corn and, consequently, affect the yield and quality of fodder. The aim of this research was to evaluate the fodder yield of three ecotypes of corn in three locations of the Loja canton with different altitudinal levels. The trial was established in the locations of: Tambo Blanco (2 668 masl), San Lucas (2 436 masl) and QEDA (2 143 masl); where the ecotypes of Criollo corn, INIAP 101 and INIAP 111, were planted under a complete randomized bifactorial design, with 9 treatments, product of the combination of genotypes and environments. Weekly, growth and development variables of the crop were recorded, from the emergence to the R3 stage, where plant height, stem elongation rate, LAI, dynamics and dry biomass accumulation rate, phenology were evaluated, together with a daily temperature record. In phenological stage R3, water content and green and dry forage yield were determined, finding statistically significant differences in ecotype x locality interaction for forage yield. The Criollo ecotype had higher green forage yield in Tambo Blanco and QEDA with 47.74 t ha-1 and 73.52 t ha-1, respectively. However, in San Lucas there were no significant differences between the Criollo and INIAP 111 ecotypes with 53.12 t ha-1 and 55.65 t ha-1, respectively, exceeding the INIAP 101 ecotype. Similarly, in dry forage yield, the Criollo ecotype showed higher values in Tambo Blanco and QEDA with 14.64 t ha-1 and 28.61 t ha-1, respectively, while in San Lucas there were no significant differences between these two ecotypes. All ecotypes increased fodder yield in the less cold environments, suggesting that genotype and thermal environment determine dry matter yield, modifying growth rate and crop cycle length. The present work highlights the superior productive characteristics of the Criollo ecotype in the three study locations. Keywords: Zea Mays L., ecotype x environment, fodder yield, phenology